Integritas Pengawasan Notaris Terhadap Calon Notaris Magang Dalam Pembuatan Akta Otentik - Habibie Rahmatullah; Budi Ispriyarso (Notarius, 2023)
AbstractA Notary Deed is a State archive that must be protected to prevent it in accordance with the provisions of the applicable legislation. The research method used in this research is doctrinal research on law. Normative-empirical law (applied law research). The contents of this discussion are about whether the Notary is responsible for the deed made by the notary apprentice candidate in carrying out the position so that it is trusted by the wider community and how the notary implementation of the apprentice Notary candidate is to prevent the Notary deed being a secret in the cyber crime notary world, the provisions in Article 15 to Article 16A Law Number 02 concerning Notary Positions of 2014 Amendments to Law Number 30 of 2004 concerning Notary Positions and based on provisions in Article 12 of the Indonesian Notary Association Regulation Number: 19/Perkum/INI/2019 concerning Internships, to avoid criminal sanctions Article 322 of the Criminal Code in accordance with the provisions of the Law on Information and Electronic Transactions in Article 6 of Law no. 11 of 2008 which states that so far the written form is identical with information and/or documents.Keywords: notary; prospective notary intern; regulation.AbstrakAkta Notaris adalah arsip Negara yang harus dilindungi untuk mencegah sesuai dengan ketentuan perundang-undangan yang berlaku. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian doktrinal dengan pendekatan normatif-empiris (applied law research). Isi pembahasan ini mengenai apakah Notaris bertanggungjawab atas akta yang dibuat oleh calon notaris magang dalam mengemban jabatan sehingga dipercaya oleh masyarakat luas dan bagaimana implementasi notaris terhadap calon Notaris magang untuk mencegah akta Notaris yang menjadi rahasia dalam dunia cyber crime notary, ketentuan pada Pasal 15 sampai dengan Pasal 16A Undang-Undang Nomor 02 Tentang Jabatan Notaris Tahun 2014 Perubahan Atas Undang-Undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris dan berdasarkan ketentuan pada Pasal 12 Peraturan Perkumpulan Ikatan Notaris Indonesia Nomor : 19/Perkum/INI/2019 Tentang Magang, untuk menghindari sanksi pidana Pasal 322 KUHP sesuai dengan ketentuan Undang-Undang Informasi dan Transaksi Elektronik  pada Pasal 6 UU No. 11 Tahun 2008 yang menyatakan  selama ini bentuk tertulis identik dengan informasi dan/atau dokumen.Kata kunci: notaris; calon notaris magang; peraturan.